2011
DOI: 10.1108/10662241111104893
|View full text |Cite
|
Sign up to set email alerts
|

Past purchase and intention to purchase in e‐commerce

Abstract: Purpose -Purchasing on the internet has unique features that make it different from the traditional shopping process, particularly with regard to its social context. This study seeks to investigate the relationship between past online purchases and purchasing intentions, representing the social context by the notions of social presence and trust. Design/methodology/approach -A sample of 115 working MBA students purchased an item online (but were stopped at the stage of paying), and then completed a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(66 citation statements)
references
References 39 publications
1
40
0
5
Order By: Relevance
“…The three items measuring intentions to obtain microcredit were adapted from Weisberg et al . () and Luarn and Lin (). Items for entrepreneurial desire were obtained from Krueger et al .…”
Section: Methodsmentioning
confidence: 98%
“…The three items measuring intentions to obtain microcredit were adapted from Weisberg et al . () and Luarn and Lin (). Items for entrepreneurial desire were obtained from Krueger et al .…”
Section: Methodsmentioning
confidence: 98%
“…In addition, Harris and Goode [16], Mantymaki and Salo [8], McCole et al [19], and Weisberg et al [20] also conducted studies in which all concluded positively the importance of online consumers' trust in e-commerce websites for driving online purchasing intention. Social presence can be infused into ecommerce websites through the creative usage of socially-rich words and photos to create human warmth, and thus, trust, in the online environment [8,14].…”
Section: Research Model 41 Perceived Trustmentioning
confidence: 96%
“…Kalakota and Robinson (1999) have argued that being competitive in terms of pricing is important for online retailers. Moreover, Hoffman and Novak (1997) suggested that Internet users get a variety of information on the Web including price al., 2013) toward the website, hence impacting on the motivational factors to shop from an e-vendor develops an affirmative outlook (Hsiao et al, 2010;Lim et al, 2011;Tang and Chi, 2005;Wang and Tseng, 2011) toward online purchase hence increases Tseng,2011; Kim et al,2004). However, customers who have a low level of trust in an e-vendor, are more likely to increase risk concerns, causing a reduction in their shopping online intention towards a particular website (Zhu,et al,2011).…”
Section: Demographic Profiling and Shmentioning
confidence: 99%